2016
DOI: 10.1097/jcp.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Peony-Glycyrrhiza Decoction for Antipsychotic-Related Hyperprolactinemia in Women With Schizophrenia

Abstract: Peony-glycyrrhiza decoction is effective in reducing antipsychotic-related hyperPRL and abnormal involuntary movement symptoms, but no reduction in blood PRL concentrations was observed. The underlying mechanisms of PGD's effects need further investigation (trial registration of NCT01852331 at www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…It appears that, while JYP had comparable efficacy in improving estrogen deprivation-induced psychiatric symptoms, JYP may possess a better safety profile than estrogen therapy. Such therapeutic advantages also have been observed in several herbal medicines that contain JYP individual materials in OVX+CUMS mice ( 16 , 17 ) and patients with menopause syndrome and hyperprolactinemia ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 69%
“…It appears that, while JYP had comparable efficacy in improving estrogen deprivation-induced psychiatric symptoms, JYP may possess a better safety profile than estrogen therapy. Such therapeutic advantages also have been observed in several herbal medicines that contain JYP individual materials in OVX+CUMS mice ( 16 , 17 ) and patients with menopause syndrome and hyperprolactinemia ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies in cultured cells and animals suggested that PGD, a famous traditional Chinese decoction, would be effective in reducing the symptoms of antipsychotics-related hyperprolactinemia [ 16 , 26 , 27 ]. At present, clinical trials have successfully proved that the PGD can significantly reduce the symptoms of hyperprolactinemia caused by antipsychotic drugs [ 19 ]. However, the majority of the studies focused on the hyperprolactinemia induced by Risperidone, Sulpiride, and Olanzapine [ 28 30 ]; the data describing the Amisulpride-induced hyperprolactinemia were rare, which may be associated with its infrequent use in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that the level of PRL may be related to the regulation of hormones, and the PGD may inhibit the secretion of PRL by regulating the hormones level [ 26 ]. However, some scholars said that although the PGD can improve the symptoms of hyperprolactinemia caused by antipsychotics, the level of PRL did not change significantly [ 19 ]. The possible reason may be related to normalization of sex hormone dysfunction via dopaminergic action upon the hypothalamic-pituitary-gonadal axis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have suggested the existence of therapeutic benefits of TCM for persistent negative symptoms, cognitive impairment, and adverse side effects in schizophrenic patients 31 . It also could alleviate hyperprolactinemia in schizophrenic patients too 32 . However, it is also commonly observed that herbal medicines are accompanied by their own risks, side-effect profile, and in some cases may inadvertently induce psychosis in schizophrenia along with unknown herb-drug interactions 33 .…”
Section: Discussionmentioning
confidence: 99%